Inclusion in Army : A Study of Acceptance of Women Leaders by Men in Uniform - Munshi, Anupama; Pandey, Suruchi (Prabandhan: Indian Journal of Management, 2017)
Inclusion is the order of the day. No organization is going to reach its full potential until there is a climate of inclusion in it. Traditionally, though some organizations, like the military, are branded as male organizations, but with the passage of time, even these organizations are expanding their boundaries and the mindset of people in them is evolving. With this underlying idea, this paper sought to understand the level of acceptance of military men for women officers in the Indian Army. The entry of women in the Indian Army is limited to the Officer Cadre in supporting Arms and Services. The paper was based on a systematic literature review and primary data collected from respondents to understand their mindset towards the acceptance and inclusion of women in the Indian Army.